The impact of plastic pollution on environmental health: An ethical and policy perspective - Mapungwana, Pheyiye; Rathebe, P. C. (Orapuh Journal, 2025)
Introduction This research investigates the urgent environmental crisis, focusing particularly on the detrimental effects of plastic pollution and its ecological impact. As environmental degradation accelerates, understanding the multifaceted nature of this crisis is essential for developing effective solutions. Purpose The primary aim of this study is to analyse the key drivers of the environmental crisis, emphasising the significant role that plastic pollution plays in exacerbating ecological challenges. By identifying these drivers, we seek to inform stakeholders and policymakers about the critical need for intervention. Methods To achieve this objective, we employed a systematic literature review approach, analysing 159 articles sourced from multiple academic databases. From this extensive review, we synthesised 21 relevant studies that provide insights into the relationship between human activities and environmental degradation. Results Our findings reveal that anthropogenic activities are the main contributors to the environmental crisis, with plastic pollution identified as a significant factor. The study highlights how plastics adversely affect ecosystems, wildlife, and human health. Furthermore, the research indicates that plastic pollution exacerbates climate change and contributes to biodiversity loss, creating a compounding effect on the environment. Conclusion The ethical implications of these findings underscore the necessity for immediate action to mitigate further environmental degradation. By fostering awareness and coordinated efforts among stakeholders—including governments, businesses, and communities—we can enhance momentum towards achieving the Sustainable Development Goals (SDGs). This paper not only contributes to the discourse on environmental awareness but also proposes actionable strategies to combat the ongoing crisis through an ethical lens.